ANALISIS PERILAKU NASABAH DALAM PENGGUNAAN PRODUK KEUANAGAN SYARIAH - Ananda Ihsan Alfajar; Fito Patrio, Lailatul Rahmi, Melia Gustina, Muji Rahayu, Mutia Husna, Nada Lilis Fadilah (BORJUIS: JURNAL OF ECONOMY, 2023)
This research uses a literature study method to analyze customer behavior in using sharia financial products at Sharia Banks. The literature study approach involves analyzing various written sources such as academic journals, books, articles, and related official documents. The research results show. Sharia financial products that are often used involve sharia insurance, sharia securities, sharia shares, and sharia deposits. Sharia insurance or takaful offers financial protection according to sharia principles. Sharia securities such as sukuk and sharia shares provide investment alternatives according to sharia principles. Sharia deposits, with the principle of profit sharing, provide an attractive option for customers who want to save and invest their funds. The main advantages of Islamic financial products involve  compliance  with sharia  principles, fairness, participation in tabarru' programs, and investment alternatives in accordance with Islamic values. As a result, this research makes an important contribution to understanding and increasing the acceptance of Islamic financial products in society